Prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) infections among patients admitted in critical care units in a tertiary care hospital - V., Arunkumar; R., Prabagaravarthanan; M., Bhaskar (International Journal of Research in Medical Sciences, 2017)
Background: The emergence of Methicillin-resistant Staphylococcus aureus (MRSA) infections in hospital leads to significant morbidity and mortality. Hence the present study was undertaken to estimate the prevalence of MRSA in critical care units (CCUs) at our centre. The objective of this study was to find the prevalence of MRSA infections in CCUs, to determine their antibiotic profile. And to screen for MRSA in the environment of CCUs in order to find whether they act as a source of infection. Methods: The present cross-sectional study included 100 patients admitted to various CCUs in our hospital. The clinical specimens (urine, Sputum, pus, blood and CSF) were collected from the admitted patients along with environmental samples from these CCUs. Two samples were collected from each patient and subjected to culture and antibiotic susceptibility testing. Results: 168 samples from 100 patients were processed. Out of which five pus samples from five different patients admitted in surgical intensive care unit (SICU) were positive for MRSA infection showing 5% prevalence in CCUs. All MRSA strains were sensitive to vancomycin and teicoplanin. Out of 30 environmental swabs, 1 swab taken from paediatric intensive care unit (PICU) showed positivity for MRSA (3%). Conclusions: CCUs in our hospital have shown 5% prevalence of MRSA among the admitted patients. There was no correlation between environmental MRSA presence and infection in the samples from patient.